Theory abundance: Social science research at the crossroads? - Paddayya, K. (University News)
Knowledge so conceived is an ocean of alternatives channelled and subdivided by an ocean of standards. It forces our mind to make imaginative choices and thus makes it grow. It makes our mind capable of choosing, imagining, and criticizing(3y(B- Reproduced s